2006
DOI: 10.1158/1535-7163.mct-05-0509
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial targeted fusion peptide exhibits remarkable cytotoxicity

Abstract: A potent cytotoxic peptide (r7-kla) was synthesized by incorporating a mitochondrial membrane disrupting peptide, kla (klaklakklaklak), with a cell-penetrating domain, r7 (rrrrrrr). The IC 50 of r7-kla (3.54 F 0.11 Mmol/L) was more than two orders of magnitude lower than that of kla. r7-kla induced cell death in both in vitro and in vivo environments, and showed rapid kinetics. Within minutes, the morphologic changes in cells and mitochondrial leakage were apparent by microscopy and was consistent with rapid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 19 publications
2
91
0
Order By: Relevance
“…[21][22][23][24][25] In previous work, we took advantage of the integrin-clustering capacity of a tetravalent cRGD-containing peptide 26 to generate more effective antagonists with augmented specificity for tumors, [27][28][29][30] improved cellular uptake, 31,32 and enhanced toxicity upon association with proapoptotic peptides. 33,34 The tumor-targeted delivery of cytotoxic peptides (e.g., [KLAKLAK] 2 ) was initially of interest for the treatment of tumors, [35][36][37][38] particularly melanoma, when targeted by cRGD 39 or with a cell-penetrating peptide, such as TAT. 40 However, despite promising results, no follow-up studies have been reported on these compounds, certainly because of the modest activity of (KLAKLAK) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] In previous work, we took advantage of the integrin-clustering capacity of a tetravalent cRGD-containing peptide 26 to generate more effective antagonists with augmented specificity for tumors, [27][28][29][30] improved cellular uptake, 31,32 and enhanced toxicity upon association with proapoptotic peptides. 33,34 The tumor-targeted delivery of cytotoxic peptides (e.g., [KLAKLAK] 2 ) was initially of interest for the treatment of tumors, [35][36][37][38] particularly melanoma, when targeted by cRGD 39 or with a cell-penetrating peptide, such as TAT. 40 However, despite promising results, no follow-up studies have been reported on these compounds, certainly because of the modest activity of (KLAKLAK) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As we know, kla cannot easily penetrate through the cell membrane, r7 as a delivery vector can increase the membrane-crossing ability of kla. Thus, the hybrid peptide of r7-kla showed stronger cellular uptake rate and stability due to the resistant ability to protease digestion and resulted to more cells apoptosis [45].…”
Section: Hybridizationmentioning
confidence: 99%
“…Penetratin, (R6/W3), and the glycosylated CPPs (at 50 μM; data not shown) and the KLAK cargo 31 did not decrease the number of viable cells even at 50 μM, the highest concentration which was used. It has been previously demonstrated with other KLAK analogs or with other cell lines that KLAK peptides are unable to cross the bilayer of eukaryotic cells unless they are coupled to a CPP [31] or a scaffold [32], which shuttle KLAK inside cells. The extent of cell death induced by all of the CPP-KLAK conjugates tested herein is reported in Fig.…”
Section: Cell Viability Studiesmentioning
confidence: 99%
“…According to the strategy depicted in Scheme 1, we have synthesized glycosylated analogs of (R6/W3), in which galactose unit(s) linked via click chemistry replace(s) one, two, or the three tryptophans. We have subsequently analyzed the viability of CHO cells treated by conjugates with the proapoptotic peptide KLAK, [31][32][33] and have visualized their localizations in these cells by fluorescence.…”
Section: Introductionmentioning
confidence: 99%